Pengembangan Aplikasi AR-BIO sebagai Media Pembelajaran Pengenalan Anatomi Sistem Respirasi menggunakan Teknologi Augmented Reality - Medeline Agustine; Eriq Muhammad Adams Jonemaro; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
The online learning system is a teaching and learning activity used during the COVID-19 pandemic. The problem caused by online teaching and learning activities is the emergence of the learning boredom in students. One of the factors that causes the learning boredom is the use of media which is believed to be less supportive. The learning media that is being used is more of one way and less interactive for the students. Therefore the AR-BIO application was developed to overcome the problem of learning boredom in students. The AR-BIO application uses markerless augmented reality technology which can project the 3d images of respiratory system organs. The AR-BIO development utilizes the SDLC waterfall method, and is intended for android devices. The AR-BIO application development process includes : Needs analysis, application design, implementation, and application testing. The test results of the AR-BIO application functionality displaying all the application functional system requirements have been achieved. The results of testing the usability of the AR-BIO application using the System Usability Scale (SUS) obtained the result of 79,5 which means the application is in the acceptable category. To find out whether the use of the AR-BIO application helps reduce boredom in students, an assessment has been carried out using the Likert scale method. The results that have been obtained for the AR-BIO application effectiveness in understanding the material is on a scale of 86%. The use of the AR-BIO application supports the learning process to be more intriguing on a scale of 94%. The use of AR-BIO application in terms of higher level of interest than previous media is 90%, and the use of AR-BIO application in terms of help motivate the learning process is on a scale of 88%.